Tolerância de cultivares de feijão (Phaseolus vulgaris L) aos herbicidas Alachlor e Linuron - Fuentes , Juan Ricardo; da Silva, José Francisco; Vieira , Clibas; Condé, Alcides R (Revista Ceres, 2025)
The tolerance of the bean cultivars, ‘Carioca’, ‘Costa Rica’, ‘Negrito 897, ‘Ricobaio 1014’ and ‘Ricopardo 896, to different alachlor and linuron combinations was evaluated under greenhouse conditions. Results indicate that both herbicides reduced the growth of all cultivars, except ‘Negrito 897' which was not affected by linuron. ‘Ricobaio 1014’ and ‘Ricopardo 896’ were the most susceptible to the herbicides. There was no indication of product interaction.